Molecular characterization and expression analysis of ATP-gated P2X7 receptor involved in Japanese flounder (Paralichthys olivaceus) innate immune response. - Shuo Li; Xuejing Li; Claudio Coddou; Xuyun Geng; Junli Wei; Jinsheng Sun (PLoS ONE, 2014)
ATP-gated P2X7 receptor (P2RX7) channel is a key component for purinergic signaling and plays important roles in the innate immune response in mammals. However, the expression, molecular properties and immune significances of P2RX7 in lower vertebrates are still very limited. Here we identified and characterized a novel bony fish P2RX7 homologue cDNA, termed poP2RX7, in Japanese flounder (Paralichthys olivaceus). PoP2RX7 protein shares about 60-88% sequence similarity and 45-78% sequence identity with known vertebrate P2RX7 proteins. Phylogenetic analysis placed poP2RX7 and other P2RX7 proteins within their own cluster apart from other P2RX members. While the functional poP2RX7 channel shares structural features in common with known P2RX7 homologs, electrophysiological studies revealed that BzATP, the more potent agonist for known mammalian and fish P2RX7s, shows similar potency to ATP in poP2RX7 activation. poP2RX7 mRNA constitutively expressed in all examined tissues from unstimulated healthy Japanese flounder with dominant expression in hepatopancreas and the lowest expression in head kidney, trunk kidney, spleen and gill. poP2RX7 mRNA expression, however, was significantly induced in Japanese flounder head kidney primary cells by Poly(I:C) and bacterial endotoxin LPS stimulations. In vivo experiments further revealed that poP2RX7 gene expression was substantially up-regulated by immune challenge with infectious bacteria Edwardsiella tarda and Vibrio anguillarum. Moreover, activation of poP2RX7 results in an increased gene expression of multifunctional cytokines IL-1β and IL-6 in the head kidney primary cells. Collectively, we identified and characterized a novel fish P2RX7 homolog which is engaged in Japanese flounder innate immune response probably through modulation of pro-inflammatory cytokines expression.